Bee Venom Pharmacopuncture: An Effective Treatment for Complex Regional Pain Syndrome - Jong-Min Kim; Hyung-Joon Jeon; Hyun-Ji Kim; Chong-Kwan Cho; Hwa-Seung Yoo (Korean Pharmacopuncture Institute, 2014)
Objectives: Treating complex regional pain syndrome (CRPS) is difficult because it still does not have a recommended therapy. A 29-year-old man was diagnosed with CRPS after surgery on his 4th and 5th left toes 7 years ago. Though he had undergone diverse pain treatment, the symptoms persisted, so he visited Dunsan Korean Medicine Hospital of Daejeon University. This case report presents results on the effect of bee venom pharmacopuncture in treating patient with CRPS. Methods: Bee venom pharmacopuncture (BVP), 0.15 to 0.4 mL dosage, was administered at GB43. The treatment was applied each week for a total 14 times. The symptoms were evaluated using a numeric rating scale (NRS) and the dosage of pain medicine. Results: On the first visit, he was taking an anticonvulsant, a trycyclic antidepressant, and an analgesic. On the NRS the worst pain in the toes received a score of 8. He also complained of severe pain and hypersensitivity when the 4th and the 5th toes were touched just slightly. Other complaint included dyspepsia, rash, and depression. After treatment, on the NRS, the score for toe pain was 0, and he no longer needed to take pain medication. During the 4-months follow-up period, he has remained without pain; neither have additional symptoms appeared nor adverse events occurred. Conclusion: BVP may have potential benefits for treating patients with CRPS.